Role of keratin 24 in human epidermal keratinocytes - Min, Min (PLoS One, 2017)
Keratin 24 (K24) is a new kind of keratin genes, which encodes a novel keratin protein, K24 that bears high similarity to the type I keratins and displays a unique expression profile. However, the role of K24 is incompletely understood. In our study, we investigated the localization of K24 within the epidermis and possible functions. Keratin 24 was found to be modestly overexpressed in senescent keratinocytes and was mainly restricted to the upper stratum spinosum of epidermis. The protein was required for terminal differentiation upon CaCl(2)-induced differentiation. In vitro results showed that increased K24 in keratinocytes dramatically changed the differentiation of primary keratinocytes. It also inhibited cell survival by G1/S phase cell cycle arrest and induced senescence, autophagy and apoptosis of keratinocytes. In addition, K24 activated PKCδ signal pathway involving in cellular survival. In summary, K24 may be suggested as a potential differentiation marker and anti-proliferative factor in the epidermis.